Effect of saliva on accuracy of digital dental implant transfer using two different materials of intraoral scan bodies with different exposed lengths - Mohamed Hesham Ahmed Tawfik; Ibrahim Ramadan EL Torky; Mohamed Maamoun El Sheikh (BMC, 2024)
Abstract Background The accuracy of digital implant transfer is currently under investigation in relation to the effect of saliva, scan body material, and exposed length. Methods Six completely edentulous casts with four implant fixtures were fabricated. The four implant fixtures in each cast were placed below the crest of the ridge of the casts by 1.5 mm. The four implant fixtures were alternately attached to four implant scan bodies (PEEK) Group (I) and (TITANIUM) Group (II). For each cast, two flexible polyurethane layers with varying thicknesses were fabricated and molded on the six 3D printed identical casts after the placement of the implant fixtures in each cast for the soft tissue moulage in the cast. The six casts were alternately covered with a 2 mm and 4 mm thick layer. The six reference casts were recorded using a coordinate measurement machine (CMM) and subsequently scanned with an Intraoral scanner (MEDIT I 700). The scanning was conducted under both dry and wet conditions, with artificial saliva applied. The scanning platform consisted of two transparent acrylic boxes, and the process followed standardized scanning conditions using a digital lux meter (n = 48). The mean difference and standard deviation values (± SD) between the implant scan bodies measured on the reference and experimental scans were calculated using the inspection software program (Medit design). Data were fed to the computer and analyzed using IBM SPSS software package version 20.0. (Armonk, NY: IBM Corp). The Kolmogorov-Smirnov test and Shapiro-Wilk test were used to verify the normality of distribution. Quantitative data mean and standard deviation. The significance of the obtained results was determined at the 5% level. The student t-test for normally distributed quantitative variables was used to compare the two groups studied. Results Statistically significant differences in wettability condition discrepancies were found between groups (I) and (II) (p < 0.05). In addition, there were statistically significant differences in intraoral scan body (ISB) length between the two groups (p < 0.05). Regarding the intraoral scan body material, statistically significant differences were found between the two groups (p < 0.05). Conclusions The presence of saliva significantly affects the accuracy of the digital implant transfer. Additionally, using a longer intraoral scan body improves the accuracy of digital implant impressions. The titanium scan body had a greater level of precision on the implant impression scan.